The Epidemiology of Primary Headache Disorders - Kopel, David; Gottschalk, Christopher (Seminars in Neurology, 2022)
Defining the epidemiology of headache disorders is challenging given the prevalence of stigma and other harmful misconceptions about these diseases. Understanding the widespread impact of these disorders is essential when considering social and policy interventions to mitigate that impact. Tension-type headache is still widely considered the most common primary headache disorder, but population-based estimates of its prevalence vary widely. Migraine remains the most common headache disorder in patients who present for clinical care. Prevalence estimates have remained fairly stable over the last two decades (1-year period prevalence, United States: 18% of women and 6% of men). Recent studies indicate that people who identify as American Indian/Alaskan Native (AI/AN) have the highest migraine prevalence of any ethnic group surveyed, particularly among AI/AN men (15% vs. <10%). Studies in the United States also show an inverse relationship between income level and migraine incidence and prevalence, particularly for chronic migraine; factors mediating this relationship are difficult to define. There are many diseases comorbid with migraine, more so with migraine with aura. The burden of migraine is enormous: the Global Burden of Disease study indicates migraine is the number 1 cause of disability in women younger than 50 years and the number 2 or 3 cause of disability worldwide. Further study is needed into underdiagnosis, undertreatment, and persistent stigma associated with headache disorders, especially in underserved communities. Stakeholders including patients, providers, and governing bodies are affected by the results of epidemiologic studies and should all have a role in crafting and evaluating thoughtful and relevant questions and hypotheses in this field.
Keywords: migraine prevalence; disease burden; quality of life; healthcare disparities; comorbidities